CSRR Loaded Compact Quad-Element MIMO Antenna for Wireless Applications - Saurabh A.K.; Srivastava S.K.; Meshram M.K. (My University, 2025)
In this paper, an extremely compact CSRR loaded triple-band quad-element MIMO antenna is proposed. The single element of the proposed MIMO antenna consists of an asymmetric T-shaped monopole antenna printed on the partial ground plane, fed through a 50O microstrip line having dual quarter wavelength inverted L-shaped slits. The orthogonal symmetric placement of the single antenna forms an extremely compact quad-element MIMO antenna. A CSRR is loaded on its ground plane at the center of the antenna for reducing the coupling. The proposed MIMO antenna covers-10 dB impedance bandwidth of 2.40-2.48 GHz, 3.47-3.57 GHz, and 4.82-7.53 GHz with a minimum isolation value of 16.5 dB in the covered triple-band. © 2021 IEEE.